Manager Resilience and The Formation of Networks: Effects of the Strategic Priority of Innovation - Ilse Maria Beuren; Tayse Gomes (BBR: Brazilian Business Review, 2022)
This study analyzes the influence of manager's resilience in networks formation under the moderating effect of the strategic priority of innovation. A survey was conducted with managers of Brazilian incubated companies, producing a sample of 106 valid responses. Data analysis was performed using the partial least squares structural equation modeling. The results showed that managers with resilient characteristics tend to attract the interest of agents to form networks. The moderating variable strategic priority of innovation affects the strength of the relationship between manager's resilience and the formation of netwrosk, being positive for the prospector strategy and negative for the defender strategy. From the results, it is possible to conclude that the attitudinal actions of managers are reflected in the expansion of the organizational structure of incubated companies and in the construction of alliances and cooperation projects.